Spillovers from Costly Credit - Melzer, Brian T (Review of Financial Studies, 2018)
Low-income households with proximate access to payday loans exhibit greater economic distress, higher take-up of food assistance benefits, and greater delinquency on child support payments than peers without proximate loan access. These findings suggest that borrowing can exacerbate distress, leading borrowers to use transfer programs and to prioritize payday loan payments over other liabilities like child support. In that way, payday lending produces negative externalities—costs imposed on taxpayers that fund transfer programs and nonresident family members that fail to receive child support. Received August 13, 2014; editorial decision December 5, 2016 by Editor Alexander Ljungqvist. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.